2016
DOI: 10.1007/s12185-016-2048-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms of cell adhesion-mediated drug resistance in multiple myeloma

Abstract: Multiple myeloma cells acquire the resistance to anti-cancer drugs through physical and functional interactions with the bone marrow microenvironment via two overlapping mechanisms. First, bone marrow stromal cells (BMSCs) produce soluble factors, such as interleukin-6 and insulin-like growth factor-1, to activate signal transduction pathways leading to drug resistance (soluble factor-mediated drug resistance). Second, BMSCs up-regulate the expression of cell cycle inhibitors, anti-apoptotic members of the Bcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 120 publications
1
46
0
Order By: Relevance
“…5 MM cells in contact with BMSCs and extracellular matrix components escape the effects of therapy through cell adhesion-mediated drug resistance. 6,7 MM-PCs achieve this by means of molecules of the integrin family, CD44, Syndecan-1 (CD138), Lymphocyte Function-Associated Antigen-1 (LFA-1), Mucin-1 antigen (MUC-1), Vascular Cell Adhesion Molecule-1 (VCAM-1) and Intercellular Adhesion Molecule-1 (ICAM-1). [8][9][10][11] In line with several observations, [12][13][14][15] Paiva et al 16 recently demonstrated that integrins and adhesion molecules are overexpressed in MM cells from patients with minimal residual disease compared with MM-PCs from newly diagnosed MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…5 MM cells in contact with BMSCs and extracellular matrix components escape the effects of therapy through cell adhesion-mediated drug resistance. 6,7 MM-PCs achieve this by means of molecules of the integrin family, CD44, Syndecan-1 (CD138), Lymphocyte Function-Associated Antigen-1 (LFA-1), Mucin-1 antigen (MUC-1), Vascular Cell Adhesion Molecule-1 (VCAM-1) and Intercellular Adhesion Molecule-1 (ICAM-1). [8][9][10][11] In line with several observations, [12][13][14][15] Paiva et al 16 recently demonstrated that integrins and adhesion molecules are overexpressed in MM cells from patients with minimal residual disease compared with MM-PCs from newly diagnosed MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…S7B for data quantification). In addition, we examined the status of EZH2 and its specific target site H3K27, because cell adhesion diminishes the abundance of H3K27me3 via EZH2 inactivation, leading to the transactivation of prosurvival genes in MM cells (5,6). As anticipated, the methylation level of H3K27 was remarkably diminished in parallel with phosphorylation and downregulation of EZH2 in MM cells under adherent and hypoxic conditions ( Fig.…”
Section: Regulation Of Cd180 Promoter By Ikzf1 Transcription Factor (mentioning
confidence: 69%
“…It is widely accepted that relapse stems from dormant and highly drug-resistant clones in the MM compartment. Drugresistant clones are kept dormant via interaction with bone marrow stroma cells (BMSC) in a hypoxic microenvironment (3)(4)(5)(6). Elucidation of the mechanisms underlying the regrowth of dormant clones may prolong remission and ultimately improve the survival of MM patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone methylation is, like DNA methylation, one of the most studied epigenetic modifications on histones. It can be linked to active transcription (e.g., H3K4me1/me2/m3, HK36me3, H3K79me1/me2/me3, H4R3me1, H4K20me1) or to gene silencing (e.g., H3K9me2/me3, H3K27me3) [10,11]. Histone methyltransferases (HMT) use, as DNMTs, the SAM cofactor to mono-, di- or tri-methylate lysine residues (thus known as HKMT, histone lysine methyltransferases) or to mono- or di-methylate arginine residues (thus known as PRMT, protein arginine N -methyltransferases) of the core or tails of histones [12].…”
Section: Introductionmentioning
confidence: 99%